El Aula Inteligente: una experiencia educativa innovadora - Segovia Olmo, Felipe; Beltrán Llera, Jesús; Martínez Arias, M. Rosario (Revista Española de Pedagogía, 2018)
This article deals with the design and assessment of a new instructional model called "The Intelligent Classroom" (IC). The Intelligent classroom is described in the context of educational learner-centered paradigm. The instructional design is formed by 8 dimensions: Goals, Tasks, Methods, Sequence, The Teacher, The Students, Assessment and Context. The model was applied to third year baccalaureate students attending 3 private schools in Madrid. The sample consisted of 398 subjects (216 males and 182 females). The design of assessment was quasi experimental, «control group non equivalent», with two groups corresponding to traditional teaching and the Intelligent Classroom. The dependent variable studied was academic achievement, assessed by objective tests. The results show positive effects of IC in general, as well as for different levels of achievement. Some significative differences in relation with gender were found.
THE INTELLIGENT CLASSROOM
Keywords: intelligent classroom; educational innovation; leaming community; Revista Española de Pedagogía